Comparison of Student Experiences with Different Online Graduate Courses in Health Promotion - Varnhagen, Stanley; Wilson, Douglas; Krupa, Eugene; Kasprzak, Susan; Hunting, Vali (Canadian Journal of Learning and Technology, 2005)
The purpose of this study was to understand the experience of students as they progressed through three specific online graduate courses in health promotion studies delivered primarily by asynchronous computer conferencing. Focused teleconference discussions were conducted with approximately 45 students from the different courses and the transcripts subjected to qualitative analysis. Themes that emerged included what new students appreciated most when adapting to learning online, factors that contributed to learner satisfaction, and the difficulties encountered by students taking a course when the content was not as well suited to the instructional method. The findings are discussed in relation to the three components of Garrison, Anderson and Archer’s (2000) Community of Inquiry model of learning: cognitive, social and teacher presence. Implications are presented for assisting students with the process of adapting to online learning and enhancing the ‘fit’ between course content and online instructional methods.